First report of a major management target species, chironomid Paratanytarsus grimmii (Diptera: Chironomidae) larvae, in drinking water treatment plants (DWTPs) in South Korea - Jae-Won Park; Kiyun Park; Ihn-Sil Kwak (PLoS ONE, 2025)
Ensuring the supply of safe and high-quality drinking water can be compromised by the presence of chironomid larvae in drinking water treatment plants (DWTPs), which may contaminate municipal water systems through freshwater resources. Chironomids are dominant species known for their resilience to a broad range of extreme aquatic environments. This study aimed to identify the morphological characteristics and obtain genetic information of the chironomid Paratanytarsus grimmii found in the water intake source and freshwater resource of DWTPs in Korea, highlighting the potential possibility of a parthenogenetic chironomid outbreak within DWTP networks. The distribution of chironomid larvae at the water intake source site (DY) of the Danyang DWTP and the freshwater resource (ND) of the Nakdong River was investigated. A total of 180 chironomid individuals, encompassing three subfamilies and six species from six 6 genera were identified at the DY site, with Procladius nigriventris being the dominant species. At the ND site, fifty chironomid individuals, encompassing two subfamilies and six species from six genera, were identified, with Cricotopus sylvestris being the dominant species. The morphological characteristics of the head capsule, mentum, mandible, and antennae of six P. grimmii larvae collected from the DY and ND sites were characterized. DNA barcoding and phylogenetic analysis revealed distinct mitochondrial diversities between the P. grimmii larvae from DY and those from ND. These results provide crucial information for the morphological identification and DNA barcoding of the key management target chironomid P. grimmii larvae, which can be used to detect the occurrence of this chironomid species in DWTPs.